An Assessment of Microfinance in Vietnam as An Innovative Mechanism for Poverty Alleviation and Hunger Eradication - Vu, Chi (2009)
The topic of microfinance has increasingly attracted much attention from both researchers and practitioners for its significant contribution in the combat against poverty and hunger. In developing nations with high poverty rates, microfinance is highly regarded for its innovative mechanism in compared to traditional aid methods. Following this realization, this paper aims to investigate microfinance sector in Vietnam, a poor country that has been widely known to achieve striking successes in economic growth and poverty alleviation. In particular, the primary objective of this paper is to provide an overview of Vietnam microfinance landscape connected to contextual factors, structure and performance of microfinance providers as well as the needs and expectations from the demand side. Another important purpose is to explore the impacts of microfinance on poor population. To this end, the paper deploys a qualitative methodology with both deductive and instructive approaches. A wide range of secondary data was collected from trustworthy sources including The Global Microfinance Information Exchange (MIX) and Vietnam Microfinance Working Group (VMWG). Further, with an aim to investigate whether microfinance can really help the poor, primary data was collected based from a small-scale survey conducted in Thanh Hoa province, one of poorest areas in Vietnam. 43 face-to-face interviews were done with local farmers and accordingly 43 questionnaires were filled. An attempt has been made to address the issues related to Vietnam microfinance sector in terms of macro-environment; social, operational and financial performance of microfinance institutions together with demand side of targeted clients. The results indicate that current context both offers opportunities and poses challenges for Vietnam microfinance. In addition, supply side analysis demonstrates that Vietnam microfinance players are improving their performance related to both outreach and self-sustainability despite the fact that they still needs to fill the gap in the local microfinance market for unserved poor population. Related to debatable issue of trade-off between outreach and sustainability, it is found that some Vietnam microfinance institutions can achieve rising outreach aligning with increasing profitability. Further, touching on demand side, some findings demonstrate that microfinance has some positive impacts on clients' income level, asset ownership and welfare enhancement. Unfortunately, no obvious evidence is found about the link between microfinance and women empowerment. Besides, limitations of the research were realized and recommendations for Vietnam microfinance enhancement and future research were made.